1990
DOI: 10.1111/j.1471-4159.1990.tb04590.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Basis of Inhibitory Presynaptic Modulation in Rat Cortical Synaptosomes

Abstract: We have investigated the possibility that, regardless of the involvement of a second messenger system, the ultimate effect of presynaptic, receptor-activated inhibitory modulation is the opening of a K channel. With the consequent hyperpolarization of the terminal, less Ca2+ would enter and this would result in the observed diminished release of a neurotransmitter. This possibility was explored utilizing rat cortical synaptosomes that were prelabeled with either 86Rb or [3H]acetylcholine, depolarizing with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Thus, a reduction in Ca2+ entry into the nerve terminal by Ca2+ channel toxins decreases glutamate release (Pocock and Nicholls, 1992;Turner et al, 1992). In addition, receptormediated inhibition of neurotransmitter release can result either from inhibition of Ca2' channels coupled to glutamate exocytosis (Banie and Nicholls, 1993) or from the activation of presynaptic Kf channels (Zoltay and Cooper, 1990). Our results indicate that L -A P~ reduces glutamate release under the clamped depolarization produced by KCI, in which Kf channel modulation of glutamate release is ineffective.…”
Section: The Mechanism Of Presynaptic Inhibitionmentioning
confidence: 73%
“…Thus, a reduction in Ca2+ entry into the nerve terminal by Ca2+ channel toxins decreases glutamate release (Pocock and Nicholls, 1992;Turner et al, 1992). In addition, receptormediated inhibition of neurotransmitter release can result either from inhibition of Ca2' channels coupled to glutamate exocytosis (Banie and Nicholls, 1993) or from the activation of presynaptic Kf channels (Zoltay and Cooper, 1990). Our results indicate that L -A P~ reduces glutamate release under the clamped depolarization produced by KCI, in which Kf channel modulation of glutamate release is ineffective.…”
Section: The Mechanism Of Presynaptic Inhibitionmentioning
confidence: 73%
“…The inhibitory effects of 12(S)-HETE may depend on its ability to alter K+ channel conductances. It has been suggested that the activities of K+ channels are responsible for the presynaptic modulation of neurotransmitter release from synaptosomes (Zoltay and Cooper, 1990). In addition, 12-lipoxygenase products act as presynaptic inhibitors of secretion by Aplysiu sensory neurons (Piomelli et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether similar processes are relevant to the plasticity of the presynaptic nerve terminal. Studies on isolated nerve terminals (Tibbs et al, 1989;Zoltay and Cooper 1990;Barrie et al, 1991) and the squid giant axon (Robitaille and Charlton, 1992) indicate that modulation of presynaptic K + channels may be an important factor in the modulation of the presynaptic input-output relation. Phosphorylation of presynaptic K + channels may prolong presynaptic depolarizations upon incoming action potentials, and may thus lengthen the periods of Ca 2 + influx (presynaptic Ca 2 + channels involved in fast-acting transmitter secretion appear not to inactivate readily, McMahon and Nicholls, 1991) and potentiate transmitter release.…”
Section: The Relationship Between Ca 2 + -Entry Intraterminal Ca 2 +mentioning
confidence: 99%